Architectural diagrams 1 - Pyo Mi-young (Berlin DOM Publishers, 2015)
The trendsetting architect Rem Koolhaas has carried it out to perfection, whereas the next generation of international stars refined it even more, giving us the unconventional presentation of designs and ideas in the form of diagrams. This method of presentation is easy to understand when dealing with the client and can be communicated internationally, beyond language and cultural barriers - a product of our globalised world. However, diagrams are now much more than explanations and form their own discipline in creative professions connected to design and construction. What looks simple is in fact a complex matter. This title in the series Construction and Design Manual is in its second edition and assembles 384 pages of diagrams by avant-garde architects and designers who specialise in public space, landscape architecture and urban planning.
Keywords: MODELS, SITE PLANNING, DRAWINGS (AR-DRW)